Efektivitas Penerapan Pembelajaran Pendidikan Jasmani, Olahraga, Dan Kesehatan Berbasis Media Sosial - Octaviano, Panca Sukma Wijaya; Fathoni, Muhad (Jurnal Porkes, 2022)
This research intend to knowing the effectiveness of the implementation of social media-based physical sports and health education using whatsapp at SDN Angkatanlor 02. The thing that underlies this research is distance learning activities implemented by the government. Therefore, SDN Angkatanlor 02 apply learning PJOK online using social media whatsapp. But it is not yet known how the effectiveness of learning PJOK use whatsapp in SDN Angkatanlor 02. This research is a qualitative descriptive. The research samples used PJOK teacher and 30 students from class 3, 4, and 5. The data collection teqnichues used method observation, interview, and documentation. The results of this research are learning physical education, sports and health using social media whatsapp has proven to be effective at SDN Angkatanlor 02. This is proven based on: 1. Good technology access from teachers and students, 2. The ability to use technology that is qualified by teachers and students, 3. Teacher activities in good teaching styles and strategies, and 4. Student activities in learning habits using good social media.